The impact of brand equity, service quality, and organizational performance on public trust in zakat institutions: evidence from Indonesia - Edy Junaedi; Johan Budiman; Irwan Maulana; Aisyah Azzahra; AR Haikal Alkanz (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2026)
With an emphasis on the functions of organizational performance, service quality, and brand equity, this study attempts to explore the factors that influence public confidence in Indonesian zakat institutions. A survey questionnaire was used in a quantitative manner. Information was gathered from Indonesian zakat institutions' donors and recipients. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 3.0 was used to examine the study model. The findings show that public trust is significantly positively impacted by organizational performance (β = 0.198, p < 0.01) and service quality (β = 0.771, p < 0.001). Remarkably, it was discovered that public trust was not significantly impacted by brand equity (β = -0.148, p = 0.568). With a significant explanatory power, the model accounts for 63.7% of the variation in public trust. In order to establish and maintain public trust, managers of zakat institutions should place a high priority on investments in excellent service delivery and strong internal governance, including accountability and transparency. Without these fundamental components, brand-building initiatives are insufficient. This study challenges the notion that brand equity has a direct impact on trust in religious charitable contexts by highlighting service quality as the most important driver of trust in Islamic social finance institutions.